2020
DOI: 10.1002/ehf2.12882
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sST2 and catestatin levels in patients with acute worsening of heart failure: a report from the CATSTAT‐HF study

Abstract: Aims Soluble suppression of tumourigenicity 2 (sST2) and catestatin (CST) reflect myocardial fibrosis and sympathetic overactivity during the acute worsening of heart failure (AWHF). We aimed to determine serum levels and associations of sST2 and CST with in-hospital death as well as the association between sST2 and CST among AWHF patients. Methods and results A total of 96 AWHF patients were consecutively enrolled, while levels of sST2 and CST were determined and compared between non-survivors and survivors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
2
15
0
6
Order By: Relevance
“…Data collected from several studies confirm that sST2 is a strong predictor of mortality or HF rehospitalization during follow up, irrespective of other traditional clinical (e.g., NYHA class), biochemical (e.g., natriuretic peptides), or echocardiographic (e.g., ejection fraction) risk markers [44,52,56,58,59]. Another very recent study showed that elevated sST2 levels were superior to NT-proBNP in predicting in-hospital death (95% CI 3.55-16.26, p < 0.001 vs. 95% CI 1.10-3.72, p = 0.037), while another "classic", widely-used biomarkerhs-cTnI-was not significantly associated with the in-hospital mortality (95% CI 0.28-2.42, p = 0.114) [60]. Under these circumstances, we consider that a multimarker test consisting of natriuretic peptides and sST2 determination will provide incremental diagnostic and prognostic values in patients with HF (Table 2).…”
Section: St2 In Heart Failure With Reduced Ejection Fraction: a Valuamentioning
confidence: 93%
“…Data collected from several studies confirm that sST2 is a strong predictor of mortality or HF rehospitalization during follow up, irrespective of other traditional clinical (e.g., NYHA class), biochemical (e.g., natriuretic peptides), or echocardiographic (e.g., ejection fraction) risk markers [44,52,56,58,59]. Another very recent study showed that elevated sST2 levels were superior to NT-proBNP in predicting in-hospital death (95% CI 3.55-16.26, p < 0.001 vs. 95% CI 1.10-3.72, p = 0.037), while another "classic", widely-used biomarkerhs-cTnI-was not significantly associated with the in-hospital mortality (95% CI 0.28-2.42, p = 0.114) [60]. Under these circumstances, we consider that a multimarker test consisting of natriuretic peptides and sST2 determination will provide incremental diagnostic and prognostic values in patients with HF (Table 2).…”
Section: St2 In Heart Failure With Reduced Ejection Fraction: a Valuamentioning
confidence: 93%
“…Of note, sST2 concentrations are higher in HFrEF than in HFpEF, being a predictor of adverse outcomes in both HF populations (Manzano-Fernandez et al, 2011;Song et al, 2020). In patients with acute worsening of HF, higher sST2 values were also shown to be useful to identify those patients at high-risk of in-hospital death (McCarthy and Januzzi, 2018;Borovac et al, 2020). sST2 concentrations rapidly decreased after hospital admission in AHF patients with uncomplicated shortterm follow-up, while AHF patients that died within 6 months showed a significant increase of sST2 values after admission (Boisot et al, 2008;McCarthy and Januzzi, 2018).…”
Section: Interleukin 33mentioning
confidence: 99%
“…Catestatin, a pleiotropic cardioprotective peptide that counterbalances the negative effects of the sympathetic nervous system, is implicated in both the metabolic syndrome and HF[ 197 ]. Specifically, alongside sST2, our recent study suggested that catestatin plasma levels reflect myocardial fibrosis and sympathetic overactivity during the acute worsening of HF[ 198 ]. With regard to diabetes, catestatin has been shown to increase glucose uptake and up-regulate GLUT4 plasma expression in rat cardiomyocytes[ 199 ], as well as improve insulin sensitivity in mice with diet-induced obesity[ 200 ].…”
Section: Discussionmentioning
confidence: 99%